From Classicism to Modernism: Western Musical Culture and the Metaphysics of Order - Etter, Brian K. (Burlington Ashgate, 2002)
The last century has witnessed the ascendancy of the avant-garde in music. From Schoenberg to Boulez to Stockhausen, the avant-garde has defined the modern conception of musical creativity. Contemporary serious music demands the 'new' in terms of style, form and ways of listening and hearing. Implicit in this approach is the rejection of the 'old', from the Baroque to the music of the later nineteenth-century symphonists. Paradoxically, however, it is this 'old' repertoire which continues to dominate concert programmes.An exploration of this dichotomy lies at the heart of this book. Drawing on a wealth of European philosophical and musical texts, Brian Etter examines the origins of the avant-garde and its relation to modernity in tandem with the history of the tonal tradition. The aim is to understand the aesthetic issues that arise from the juxtaposition of these two approaches to music in the concert hall. A wide-ranging survey of historical texts concerned with the philosophy of music helps us to recover the concept of the metaphysical and its importance over the ages to the musical tradition in both its classicist and its modernist phases. Etter argues that metaphysical understanding is crucial for the construction of a common culture and suggests that by re-integrating it into our aesthetic approach to music, we can better understand our musical heritage and its future.
Keywords: 20th Century (1901-2000); Avant-garde; Music philosophy and esthetics